STRATEGI MENINGKATKAN KESULITAN BELAJAR BAGI ANAK USIA DINI MELALUI BERMAIN - Ramos Ria Kay (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2021)
This article describes strategies for increasing learning difficulties for early childhood through play. This article is also to find out how to treat early childhood with learning difficulties. The purpose of this article is also to determine learning difficulties for early childhood through play. Through play activities, children can organize various experiences and cognitive abilities in an effort to reconstruct their beautiful ideas. In other words, play is the initial stage of the learning process in children experienced by all humans.